2014
DOI: 10.1007/s10198-014-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of infliximab-biosimilar compared to other biological drugs in rheumatoid arthritis: a mixed treatment comparison

Abstract: ObjectiveThe aim of this meta-analysis was to compare the efficacy and safety of infliximab-biosimilar and other available biologicals for the treatment of rheumatoid arthritis (RA), namely abatacept, adalimumab, certolizumab pegol, etanercept, golimumab, infliximab, rituximab and tocilizumab.MethodsA systematic literature review of MEDLINE database until August 2013 was carried out to identify relevant randomized controlled trials (RCTs). Bayesian mixed treatment comparison method was applied for the pairwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…These data were supported by the findings of a Phase I trial in patients with ankylosing spondylitis (AS) [47]. Two metaanalyses have also confirmed that CT-P13 possesses efficacy and safety profiles similar to other biologic drugs, both in RA and AS [48,49]. In these analyses, CT-P13 was compared with several RMP biologics, namely infliximab, abatacept, adalimumab, certolizumab pegol, etanercept, golimumab, rituximab and tocilizumab.…”
Section: S46mentioning
confidence: 71%
“…These data were supported by the findings of a Phase I trial in patients with ankylosing spondylitis (AS) [47]. Two metaanalyses have also confirmed that CT-P13 possesses efficacy and safety profiles similar to other biologic drugs, both in RA and AS [48,49]. In these analyses, CT-P13 was compared with several RMP biologics, namely infliximab, abatacept, adalimumab, certolizumab pegol, etanercept, golimumab, rituximab and tocilizumab.…”
Section: S46mentioning
confidence: 71%
“…This study was done at Hammersmith Medicines Research, a clinical pharmacology unit in the UK, in accordance with the prevailing EU directives and International Conference on Harmonisation Good Clinical Practice. After review of the safety profile of adalimumab, and the safety record of monoclonal antibody studies in healthy subjects, we considered it acceptable to do the study [6,[12][13][14][15]. The study was not started until it had received approval from the Medicines and Healthcare products Regulatory Agency (MHRA; EudraCT number: 2012-005140-23), and Scotland A Research Ethics Committee (reference number: 12/SS/0220).…”
Section: Methodsmentioning
confidence: 99%
“…These drugs were registered under the same conditions as the originator infliximab for the treatment of six adult conditions and in two pediatric indications. Nevertheless, randomized clinical trials (RCT) have been carried out only in two adult rheumatic disorders: a non-inferiority study in rheumatoid arthritis and another in anklyosing spondylitis [1,2]. These studies did not find significant differences either in efficacy or in safety between the originator and the biosimilar substance [3,4].…”
Section: Introductionmentioning
confidence: 95%
“…Biosimilar infliximab drugs (brand names Remsima Ô and Inflectra Ô ) are the first biosimilar monoclonal antibody medicines in chronic inflammatory conditions approved by the European Medicine Agency in 2013 [1,2]. These drugs were registered under the same conditions as the originator infliximab for the treatment of six adult conditions and in two pediatric indications.…”
Section: Introductionmentioning
confidence: 99%